Nickel aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material as well as preparation method and application thereof

Through the combination of nickel-aluminum hydrotalcite, zinc oxide and ethylene glycol chitosan, an antibacterial material with a core-shell structure is formed, which solves the problem that the antibacterial activity of existing materials is affected by the environmental pH value, and achieves a stable antibacterial effect under different pH environments.

CN119500279APending Publication Date: 2025-02-25PANZHIHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411688719.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The antibacterial activity of existing chitosan hybrid materials is easily affected by changes in the environmental pH value, especially when pH >5 is lost.

Method used

The core-shell structure design of nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material is adopted, and nickel-aluminum hydrotalcite and zinc oxide are wrapped by ethylene glycol chitosan to form a stable antibacterial material.

Benefits of technology

The antibacterial activity of this hybrid material is not affected by changes in the environmental pH value, and even shows efficient antibacterial activity against Staphylococcus aureus, E. coli and yeast even when alkaline ambient pH values ​​are as high as 10.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500279A_ABST
    Figure CN119500279A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of hybrid materials, and particularly relates to a nickel aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material as well as a preparation method and application thereof. The invention provides a nickel aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material, which is of a core-shell structure, and takes ethylene glycol chitosan as a shell to wrap nickel aluminum hydrotalcite and zinc oxide. According to the nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material (NiAl-LDH-ZnO / GCS), nickel-aluminum hydrotalcite and zinc oxide are wrapped by ethylene glycol chitosan, and the nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material shows efficient antibacterial activity on staphylococcus aureus, escherichia coli and saccharomycetes when the pH value is higher than 6.5, including the pH value in an alkaline environment is as high as 10; under the irradiation of light with the wavelength of about 390 to 420 nm, the NiAl-LDH (at) ZnO / GCS shows strong photocatalytic antibacterial activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hybrid materials, and specifically relates to a nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material and a preparation method and application thereof. Background Art

[0002] Careless use and overconsumption of antibiotics in humans and animals have led to the emergence of drug-resistant strains, and epidemiological studies have shown that infections caused by multidrug-resistant bacteria continue to increase. The high cost of research and hospitalization has prompted the scientific community to seek other ways and means to provide effective antimicrobial materials at a lower cost, thereby developing new antimicrobial materials with higher antimicrobial activity and low environmental impact, which is critical to global health, but has proven to be challenging.

[0003] In the fight against antimicrobial resistance, the use of photoresponsive antimicrobial hybrid materials is increasing. The construction of organic-inorganic hybrid materials is a rapidly developing field in materials chemistry, aiming to produce advanced materials with improved structures and functions. Biomaterials have the advantages of non-toxicity, good thermal stability and good biocompatibility. Bio-inorganic hybrids can not only show the properties of different components, but also further enhanced properties and new synergistic properties due to the interaction between biomolecules and inorganic materials. Chitosan is a biopolymer that exhibits antimicrobial activity against a variety of microorganisms. It has three types of functional nucleophilic groups, namely C-2NH2 groups, secondary C-3OH groups and C-6 primary OH groups. Chitosan has reactive functional groups that are easy to chemically modify, and it has been shown that antioxidants / antimicrobial active substances can be covalently grafted onto its skeleton. However, the antimicrobial activity of chitosan hybrid materials prepared so far is easily affected by changes in environmental pH and loses antimicrobial activity when the environmental pH>5. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material and its preparation method and application. The nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material provided by the present invention has stable antibacterial activity and is not affected by changes in environmental pH.

[0005] The invention provides a nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material, which is a core-shell structure, with ethylene glycol chitosan as a shell to encapsulate the nickel-aluminum hydrotalcite and zinc oxide.

[0006] Preferably, the mass ratio of the zinc oxide, ethylene glycol chitosan and nickel aluminum hydrotalcite is 1:4:6 to 1:8:12.

[0007] The present invention also provides a method for preparing the nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material described in the above technical solution, comprising the following steps:

[0008] After dissolving ethylene glycol chitosan in an acidic solution, the mixture is mixed with nickel aluminum hydrotalcite and zinc oxide for self-assembly to obtain a colloidal solution;

[0009] The colloidal solution is dried to obtain a nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material.

[0010] Preferably, the acidic solution is an acetic acid solution, and the concentration of the acetic acid solution is 0.1-0.5 mol / L.

[0011] Preferably, the drying temperature is 50-60° C. and the drying time is 6-12 hours.

[0012] Preferably, the preparation method of the nickel-aluminum hydrotalcite comprises:

[0013] Nickel chloride, aluminum hydroxide, water and urea are mixed to carry out a first hydrothermal reaction to obtain nickel aluminum hydrotalcite.

[0014] Preferably, the molar ratio of nickel in the nickel chloride to aluminum in the aluminum hydroxide is 3:2 to 8:3.

[0015] Preferably, the temperature of the first hydrothermal reaction is 85-95° C. and the time is 12-15 hours.

[0016] Preferably, the Cl formed by the urea and nickel chloride - The molar ratio is 4:3 to 2:1.

[0017] The present invention also provides the use of the nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material described in the above technical solution or the nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material obtained by the above preparation method in the preparation of antibacterial materials.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention provides a nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material, which is a core-shell structure, with ethylene glycol chitosan as a shell, encapsulating nickel-aluminum hydrotalcite and zinc oxide. The present invention combines nickel-aluminum hydrotalcite, zinc oxide and ethylene glycol chitosan into a hybrid material for the first time to form a core-shell structure, and ethylene glycol chitosan encapsulates nickel-aluminum hydrotalcite and zinc oxide. The antibacterial activity of the hybrid material is not easily affected by the environment, and when the pH value of the alkaline environment is as high as 10, it exhibits efficient antibacterial activity against Staphylococcus aureus, Escherichia coli and yeast. The nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material (NiAl-LDH@ZnO / GCS core-shell material) provided by the present invention improves the light-responsive antibacterial activity of the hybrid material by combining NiAl-LDH, ZnO and GCS, and better eliminates pathogenic microorganisms. The hybrid material of the present invention maintains activity in the visible light range above 390nm, and enhances the light-responsive antibacterial activity of chitosan, avoiding the situation where there is no antibacterial activity when pH>5. The antibacterial hybrid material synthesized by the present invention has the advantages of good thermal stability, low sensitivity to the medium, persistent surface charge, relatively low viscosity, high light-responsive antibacterial activity, and a simple preparation method and low cost, and has a good application prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 The XRD pattern of the core-shell material in the embodiment;

[0022] Figure 2 TEM spectrum of the core-shell material in the embodiment;

[0023] Figure 3 FTIR spectrum of the core-shell material in the embodiment;

[0024] Figure 4 The UV-Vis DRS spectrum of the core-shell material in the embodiment;

[0025] Figure 5 This is the SEM image of the core-shell material in the embodiment;

[0026] Figure 6 is the TGA-DTG spectrum of the core-shell material in the embodiment;

[0027] Figure 7 It is the BET-BJH diagram of the hybrid material in the embodiment;

[0028] Figure 8 The antibacterial effects of GCS, ZnO, NiAl-LDH and NiAl-LDH@ZnO / GCS on Escherichia coli in the dark and in the light, with the left picture showing the effect of light and the right picture showing the effect of no light;

[0029] Fig. 9 The antibacterial effects of GCS, ZnO, NiAl-LDH and NiAl-LDH@ZnO / GCS on Staphylococcus aureus in the dark and in the light, with the left picture showing the effect of light and the right picture showing the effect of no light;

[0030] Fig.10 The antibacterial effect of GCS, ZnO, NiAl-LDH and NiAl-LDH@ZnO / GCS on yeast in darkness and light, where A is under the action of light and B is under the action of no light;

[0031] Fig.11 The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) results of NiAl-LDH@ZnO / GCS. DETAILED DESCRIPTION

[0032] The invention provides a nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material, which is a core-shell structure, with ethylene glycol chitosan as a shell to encapsulate the nickel-aluminum hydrotalcite and zinc oxide.

[0033] In the present invention, the mass ratio of zinc oxide (ZnO) to nickel aluminum hydrotalcite (NiAl-LDH) is preferably 0.5:3-2:9, glycol chitosan (GCS) is protected and retains its antibacterial potential in the composite hybrid material, and its light-responsive antibacterial activity is also enhanced.

[0034] In the present invention, the mass ratio of zinc oxide, ethylene glycol chitosan and nickel aluminum hydrotalcite is preferably 1:4:6 to 1:8:12, more preferably 1:4:6.

[0035] The present invention also provides a method for preparing the nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material described in the above technical solution, comprising the following steps:

[0036] Dissolving ethylene glycol chitosan in an acid solution, and then mixing with nickel aluminum hydrotalcite and zinc oxide for self-assembly to obtain a colloidal solution;

[0037] The colloidal solution is dried to obtain a nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material.

[0038] In the present invention, unless otherwise specified, the materials and equipment used are commercially available products in the art.

[0039] In the present invention, the preparation method of the nickel-aluminum hydrotalcite preferably comprises:

[0040] Nickel chloride, aluminum hydroxide, water and urea are mixed to carry out a first hydrothermal reaction to obtain nickel aluminum hydrotalcite (nickel aluminum layered double hydroxide, NiAl-LDH).

[0041] In the present invention, the molar ratio of nickel in the nickel chloride to aluminum in the aluminum hydroxide is preferably 3: 2 to 8: 3, more preferably 1.8: 1. In the molar ratio of the present invention, the concentration of aluminum hydroxide is lower than that of nickel chloride, the obtained hydrotalcite has good crystallinity, and the obtained hybrid material has good antibacterial properties.

[0042] In the present invention, the Cl - The molar ratio of is preferably 4:3 to 2:1, and specifically 1.6:1 。 The nickel-aluminum hydrotalcite obtained by adding urea in the present invention has a composite material with uniform particle size.

[0043] In the present invention, the nickel chloride, aluminum hydroxide, water and urea are preferably mixed in the following manner: nickel chloride, aluminum hydroxide and water are first mixed, and then mixed with urea. The first mixing and the second mixing are preferably stirred, the first mixing time is preferably 15 to 20 minutes, and the second mixing time is preferably 10 to 15 minutes; the amount ratio of the nickel chloride, aluminum hydroxide, water and urea is preferably 4.2784g:1.4486g:120mL:6.4864g, and the nickel chloride, aluminum hydroxide, water and urea are mixed to obtain a transparent solution.

[0044] In the present invention, the temperature of the first hydrothermal reaction is preferably 85-95°C, more preferably 90°C, and the time is preferably 12-15h. After the first hydrothermal reaction, the steps of cooling, washing and drying the obtained solid are preferably performed; the temperature after cooling is preferably room temperature; the washing preferably includes washing with deionized water and washing with anhydrous ethanol; the drying temperature is preferably 60-80°C, and the time is preferably 12-18h.

[0045] In the present invention, the pH value is preferably controlled to be 6.5-9 during the preparation of the nickel-aluminum hydrotalcite.

[0046] Nickel aluminum hydrotalcite (NiAl-LDH) is a heterogeneous structure nanomaterial, which is composed of positively charged brucite-type divalent and trivalent metal hydroxide layers, has excess positive charge, has strong photocatalytic ability, and can improve the stability of hybrid materials. After loading zinc oxide, the hybrid material has excellent photocatalytic, mildew-proof and antibacterial abilities. Moreover, the preparation method of the nickel aluminum hydrotalcite of the present invention is simple and low-cost.

[0047] In the present invention, the method for preparing zinc oxide preferably comprises:

[0048] Alkaline solution and ethylene glycol solution of zinc acetate are mixed to carry out precipitation reaction, and the obtained reaction solution is subjected to a second hydrothermal reaction to obtain zinc oxide; the alkali solution includes sodium hydroxide solution or potassium hydroxide solution.

[0049] In the present invention, the concentration of zinc acetate in the ethylene glycol solution of zinc acetate is preferably 1.024-1.035 g / 120 mL; the ethylene glycol solution of zinc acetate is obtained by mixing zinc acetate and ethylene glycol, the mixing is preferably stirred in a water bath, the temperature of the water bath is preferably 60-70° C., and the stirring time is preferably 1 hour.

[0050] In the present invention, the alkali solution is preferably a sodium hydroxide solution, the concentration of the sodium hydroxide solution is preferably 0.3 mol / L, and the volume ratio of the zinc acetate ethylene glycol solution to the sodium hydroxide solution is preferably 6: 1. After the dropwise addition, stirring in a water bath is preferably included, the temperature of the water bath is preferably 70-80° C., and the time is preferably 3-4 hours.

[0051] In the present invention, the temperature of the second hydrothermal reaction is preferably 120-160°C, and the time is preferably 24-36 hours. After the second hydrothermal reaction, it is preferred to further include: washing the obtained solid, drying and grinding; the washing preferably includes anhydrous ethanol washing and deionized water washing, and the number of anhydrous ethanol washing and deionized water washing is preferably 3-5 times independently; the drying temperature is preferably 60-80°C, and the time is preferably 12-18 hours. The present invention has no special requirements for the grinding method, and the method commonly used by those skilled in the art can be used.

[0052] The zinc oxide (ZnO) nano material prepared by the invention has good antibacterial performance against Gram-positive bacteria and Gram-negative bacteria.

[0053] In the present invention, the preparation method of ethylene glycol chitosan preferably comprises:

[0054] The alkaline solution of chitosan and the alkaline solution of ethylene glycol are mixed to react, and the solid and liquid are separated to obtain ethylene glycol chitosan.

[0055] In the present invention, the alkaline solution in the alkaline solution of chitosan and the alkaline solution of ethylene glycol are preferably sodium hydroxide solutions, and the concentration of the sodium hydroxide solutions is preferably 1 wt %.

[0056] In the present invention, the mass ratio of chitosan to ethylene glycol is preferably 5:(1-1.5), more preferably 5:1.3.

[0057] In the present invention, the reaction temperature is preferably 60-70° C., and the reaction time is preferably 18 hours. During the reaction, the hydrophilic side chains of ethylene glycol combine with the amino groups of chitosan, and the resulting polymer is soluble in water at a neutral / acidic pH value.

[0058] In the present invention, the reaction preferably further comprises: dripping hydrogen peroxide; the concentration of the hydrogen peroxide is preferably 30wt%, the ratio of hydrogen peroxide to chitosan is preferably 40mL:0.5g, and the reaction system is preferably stirred for 3-4h after dripping hydrogen peroxide.

[0059] In the present invention, the solid-liquid separation method is preferably suction filtration, and the solid-liquid separation preferably also includes drying, and the drying temperature is preferably 60°C.

[0060] The glycol chitosan (GCS) prepared by the present invention is low-acetylation chitosan with a deacetylation degree of 90-99.5%. The present invention converts chitosan into glycol chitosan to make it more soluble, and then combines the glycol chitosan into a hybrid material in the form of a core-shell, thereby solving the problem of reduced antibacterial activity of chitosan with a deacetylation degree of less than 95%.

[0061] The glycol chitosan (GCS) prepared by the present invention has an amino group pKa value of about 6.5, can produce significant protonation in a neutral solution, and is beneficial to improving the light-responsive antibacterial efficiency of ZnO. GCS has a large number of primary amines and hydroxyls, has a high affinity for metal ions, and is an excellent carrier of layered double hydroxide (LDH).

[0062] After obtaining nickel aluminum hydrotalcite, zinc oxide and ethylene glycol chitosan, the present invention dissolves the ethylene glycol chitosan in an acidic solution, and then mixes the solution with the nickel aluminum hydrotalcite and zinc oxide for self-assembly to obtain a colloidal solution.

[0063] In the present invention, the acidic solution is preferably an acetic acid solution, and the concentration of the acetic acid solution is preferably 0.1 to 0.5 mol / L. The yield of the hybrid material obtained by the acetic acid solution concentration of the present invention is high, which is about 3 times the amount of the product obtained when the acetic acid concentration is higher than 0.5 mol / L, and the obtained hybrid material has good antibacterial properties.

[0064] In the present invention, the method of dissolving the ethylene glycol chitosan in the acidic solution is preferably stirring, and the stirring time is preferably 3 to 4 hours. The pH value of the ethylene glycol chitosan acidic solution obtained by dissolving the ethylene glycol chitosan in the acidic solution is preferably 5, and the concentration of the ethylene glycol chitosan is preferably 0.2wt%. The method of mixing the ethylene glycol chitosan acidic solution with nickel aluminum hydrotalcite and zinc oxide preferably includes stirring and ultrasound, and the stirring time is preferably 6 to 10 hours, more preferably 6.3 hours, and the ultrasound time is preferably 10 to 15 minutes. After the mixing, the nickel aluminum hydrotalcite and zinc oxide are dispersed in the ethylene glycol chitosan acidic solution, and self-assemble to form a core-shell structure. At the same time, the ethylene glycol chitosan has an adhesive effect, interacts with NiAl-LDH and ZnO through numerous amino groups, and contributes hydroxyl groups in a solution with a pH value of about 5. The free electron doublet on nitrogen combines with metal cations under the regulation of the pH value of the solution. The protonation of the amine group in the acidic solution makes the polymer have cationic behavior, thereby having the potential to attract metal anions. Soft acid media are favorable for ions to interact with other ions or ligands or to form coordination bonds. A possible mechanism for the formation of core-shell composites is the "bridge model," in which metal ions are linked to several amine groups of the same or different chains through intermolecular or intramolecular complexes.

[0065] After obtaining the colloidal solution, the present invention dries the colloidal solution to obtain the nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material.

[0066] In the present invention, the drying temperature is preferably 50-60° C., and the drying time is preferably 6-12 hours, more preferably 7 hours.

[0067] The nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material prepared by the present invention has a large pore size. Under lightless conditions, the pores absorb bacteria and release metal oxides and ion particles in the medium. Ethylene glycol chitosan has higher solubility in the mixed material, inhibits microbial growth through zinc oxide, enhances the chelating effect, and interferes with the negatively charged bacterial cell membrane. Chitosan interacts with the bacterial membrane, resulting in impaired cell permeability and membrane lysis. Sterilization under light activation uses light irradiation of appropriate wavelengths, ranging from ultraviolet (UV) to near infrared (NIR), activates the light-responsive material, absorbs light energy, and effectively kills pathogens in a short time by generating free radical oxygen species (ROS) or / and high temperature conditions.

[0068] The present invention also provides the use of the nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material described in the above technical solution or the nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material obtained by the above preparation method in the preparation of antibacterial materials.

[0069] The nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material (NiAl-LDH@ZnO / GCS core-shell material) provided by the present invention improves the light-responsive antibacterial activity of the hybrid material by combining NiAl-LDH, ZnO, and GCS, and better eliminates pathogenic microorganisms. The hybrid material of the present invention maintains activity in the visible light range above 390nm, and enhances the light-responsive antibacterial activity of chitosan, avoiding the situation where there is no antibacterial activity when the pH value is >5 or the deacetylation degree (DD) of chitosan is less than 95%. The antibacterial hybrid material synthesized by the present invention has the advantages of good thermal stability, low sensitivity to the medium, persistent surface charge, relatively low viscosity, and high light-responsive antibacterial activity, and the preparation method is simple and low cost, and has a very high application prospect.

[0070] To further illustrate the present invention, the nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material provided by the present invention and its preparation method and application are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.

[0071] Example 1 Preparation of NiAl-LDH Material

[0072] The nickel-aluminum hydrotalcite material was prepared by the reactor hydration method: 4.2784 g of nickel chloride was added with 1.4486 g of aluminum hydroxide and mixed with 120 mL of deionized water. After magnetic stirring for 15 minutes, 6.4864 g of urea was added, and then magnetic stirring was continued for 15 minutes to obtain a uniform and transparent solution.

[0073] The obtained solution was then transferred to a 200 mL Teflon-lined hydrothermal reactor and reacted at 90°C for 12 hours. After the reaction was completed, it was cooled to room temperature, taken out, repeatedly rinsed with deionized water and anhydrous ethanol, and dried in an oven at 60°C for 12 hours to finally obtain nickel aluminum hydrotalcite (NiAl-LDH) material.

[0074] Example 2 Preparation of ZnO material

[0075] ZnO is prepared by direct precipitation method and hydrothermal synthesis method. The specific operation is as follows:

[0076] 1.024 g of zinc acetate was weighed and added to 120 mL of ethylene glycol. The mixture was stirred in a water bath at 70 °C for 1 h. 20 mL of 0.3 mol / L NaOH solution was added dropwise to the mixed solution. The mixture was stirred in a water bath at 70 °C for 4 h. The mixture was then loaded into a reactor and subjected to hydrothermal reaction at 160 °C for 24 h. After the reaction was completed, the mixture was taken out and washed with anhydrous ethanol and deionized water for 3 times respectively. The mixture was dried at 60 °C and ground to obtain a pure ZnO sample.

[0077] Example 3 Preparation of ethylene glycol chitosan material

[0078] Ethylene glycol chitosan was prepared by chemical synthesis. The specific steps are as follows:

[0079] 0.5 g of chitosan was dissolved in 1% (w / v) sodium hydroxide solution (100 mL) to obtain a uniform chitosan solution; then 0.13 g of ethylene glycol was mixed with 1% (w / v) sodium hydroxide solution (100 mL) and heated to a specified temperature of 60°C; then the chitosan solution was slowly added to the mixture of ethylene glycol and sodium hydroxide at room temperature, and after stirring for 18 hours, 40 mL of 30 wt% hydrogen peroxide was added dropwise to the reaction solution, and the temperature was kept constant and stirred; finally, the reaction was stopped after stirring for 4 hours, and then the solution was cooled to room temperature for 12 hours, filtered, and dried in a 60°C drying oven to obtain a crude product of ethylene glycol chitosan (GCS).

[0080] Example 4 Preparation of NiAl-LDH@ZnO / GCS core-shell material

[0081] When preparing NiAl-LDH@ZnO / GCS, the crude ethylene glycol chitosan obtained in Example 3 was dissolved in 0.1 mol / L acetic acid, magnetically stirred at room temperature for 3 hours to completely dissolve it, and the pH value was adjusted with sodium hydroxide solution to obtain a 0.2wt% GCS solution with a pH value of 5. The ZnO nanoparticles obtained in Example 2 and the NiAl-LDH obtained in Example 1 were dispersed in a 0.2wt% GCS solution, and the mass ratio of ZnO / GCS / NiAl-LDH was 1:4:6. After stirring for 6 hours and 20 minutes, the solution was ultrasonically treated for 15 minutes. Finally, a highly dispersed colloidal solution was obtained, which was dried in an oven at 60°C for 12 hours to obtain a NiAl-LDH@ZnO / GCS core-shell material.

[0082] Test Example 1 Determination of antibacterial activity of hybrid material (NiAl-LDH@ZnO / GCS core-shell material)

[0083] The bacteria used as target organisms were Escherichia coli (E. coli, Gram-negative bacteria), Staphylococcus aureus (Staphylococcus aureus, Gram-positive bacteria) and Yeast (Yeast, fungi), AS3.4513, all from the Microbial Collection Center of Xiangtan University.

[0084] Yeast yeast was maintained in potato dextrose (PD) medium at 28°C for 72 hours. Escherichia coli and Staphylococcus aureus strains were maintained in mineral salt (MS) medium at 37°C, pH 7.0 for 24 hours. All samples were measured to obtain their OD600nm values ​​to calculate the inhibitory concentration. The control test included a nutrient medium with a bacterial suspension but without an antibacterial agent (NiAl-LDH@ZnO / GCS core-shell material).

[0085] The antimicrobial efficiency of the NiAl-LDH@ZnO / GCS core-shell material was evaluated by determining the antimicrobial sensitivity of bacteria after exposure to the test samples using the agar well diffusion method. Gram-negative Escherichia coli and yeast were used as target organisms. All antimicrobial experiments involving both cultures were performed in sterile 250 mL shake flasks or 90 mm agar plates. In fact, for antimicrobial testing, 100 mL of the culture portions of Cyclospora and E. coli strains were transferred to PD and MS media. The plates were incubated at 37 °C for 24 h in E. coli and at 28 °C for 72 h in Cyclospora. Finally, the inhibition zone (in millimeters) around the wells was measured to evaluate the antimicrobial activity. The results are shown in Table 1 and Figures 1 to 11 shown.

[0086] Table 1 Antibacterial activity of NiAl-LDH@ZnO / GCS core-shell materials

[0087]

[0088] Figure 1 The XRD pattern of the core-shell material (NiAl-LDH@ZnO / GCS) in the embodiment; Figure 2 This is the TEM spectrum of NiAl-LDH@ZnO / GCS; the TEM image confirms that the morphology of the NiAl-LDH@ZnO / GCS hybrid is a core-shell type, with nickel aluminum hydrotalcite and zinc oxide evenly distributed, and ethylene glycol chitosan acting as a binder and shell, indicating the formation of a hybrid based on NiAl-LDH, ZnO and GCS.

[0089] Figure 3 The FTIR spectra of the core-shell materials in the examples are GCS, NiAl-LDH, ZnO and NiAl-LDH@ZnO / GCS core-shell materials from bottom to top, indicating that GCS and NiAl-LDH have been incorporated into the NiAl-LDH@ZnO / GCS hybrid and affect the structure of the NiAl-LDH@ZnO / GCS hybrid, and GCS, NiAl-LDH and ZnO have been combined to form a NiAl-LDH@ZnO / GCS composite.

[0090] Figure 4 The UV-Vis DRS spectra of the core-shell materials in the examples are shown in Figure 1. The black line represents ZnO, the red line represents GCS, the blue line represents NiAl-LDH, and the green line represents the NiAl-LDH@ZnO / GCS composite material. The core-shell NiAl-LDH@ZnO / GCS has significant differences in light absorption from ultraviolet to infrared regions, with a maximum absorption peak at 374nm, but the absorption value increases continuously in the range of 531nm to 692nm, and the absorption value at 800nm ​​is 0.016au.

[0091] Figure 5 : SEM images of the core-shell materials in the examples, wherein A is GCS, B is NiAl-LDH, C is ZnO and D is NiAl-LDH@ZnO / GCS (×200 nm), and the scale bar in the figure is 200 nm.

[0092] Figure 6 The TGA-DTG spectrum of the core-shell material in the embodiment (thermogravimetric and differential thermogravimetric TGA-DTG curves of NiAl-LDH@ZnO / GCS); It can be seen from the curve spectrum of the NiAl-LDH / ZnO / GCS mixture that even if the addition of CS affects the thermal stability of the obtained core-shell material, it still remains stable at high temperatures (30-800°C).

[0093] Figure 7 The BET-BJH diagram of the hybrid material in the embodiment, where the upper figure is BET and the lower figure is BJH; the specific surface area, pore volume and pore size of the NiAl-LDH@ZnO / GCS core-shell material are S BET =9.235m 2 g -1 、V P =0.053cm 3 g -1 , D P =22.649nm, indicating that the D p The average particle size of the nanoparticles is 64.7 nm.

[0094] Figure 8 These are the antibacterial effects of GCS, ZnO, NiAl-LDH and NiAl-LDH@ZnO / GCS (composite material) on Escherichia coli in darkness and light, where the left picture is under the action of light and the right picture is without light (darkness). Fig. 9 These are the antibacterial effects of GCS, ZnO, NiAl-LDH and NiAl-LDH@ZnO / GCS (composite material) on Staphylococcus aureus in darkness and light, where the left picture is under the action of light and the right picture is under the action of no light. Fig.10 The antibacterial effect of GCS, ZnO, NiAl-LDH and NiAl-LDH@ZnO / GCS (composite material) on yeast in darkness and light, where A (first row) is under light action and B (second row) is without light action. The results show that ZnO exhibits strong antibacterial activity in the dark, while the hybrid NiAl-LDH@ZnO / GCS exhibits the best light-responsive antibacterial activity against yeast, Staphylococcus aureus and Escherichia coli. The results also show that NiAl-LDH@ZnO / GCS can maintain and improve its antibacterial ability in cell culture media with a pH value higher than 6 (pH 6-9).

[0095] Fig.11 The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) results of NiAl-LDH@ZnO / GCS, from top to bottom, are the effects on Escherichia coli, Staphylococcus aureus and yeast. The minimum inhibitory concentration (MIC) of NiAl-LDH@ZnO / GCS composite material for Escherichia coli under light conditions is 28g / L and the minimum bactericidal concentration (MBC) is 32g / L. The minimum inhibitory concentration (MIC) of NiAl-LDH@ZnO / GCS composite material for Staphylococcus aureus under light conditions is 26g / L and the minimum bactericidal concentration (MBC) is 30g / L. The minimum inhibitory concentration (MIC) of NiAl-LDH@ZnO / GCS composite material for yeast under light conditions is 2g / L and the minimum bactericidal concentration (MBC) is 4g / L.

[0096] It can be seen from the above results that the NiAl-LDH@ZnO / GCS core-shell material was prepared by the method of the present invention, and its antibacterial activity is better than that of GCS, ZnO and NiAl-LDH. It was also found that with the increase of the concentration of GCS and NiAl-LDH, the light responsiveness of the synthesized core-shell material is enhanced, and the light responsive antibacterial activity is also enhanced. Therefore, when preparing the hybrid material of the present invention, it is necessary to strictly require the concentration of GCS and NiAl-LDH. The present invention synthesizes a hybrid photoresponsive material for antibacterial purposes. In order to enhance the light-responsive antibacterial hybrid material, the antibacterial activity exhibited by the hybrid material under light conditions is much better than the antibacterial activity of each component itself, and has important economic value.

[0097] The present invention combines nickel aluminum hydrotalcite (NiAl-LDH), zinc oxide (ZnO) and ethylene glycol chitosan for the first time, and the obtained antibacterial hybrid material is a core-shell structure. NiAl-LDH provides a large number of pores, has a good ability to fix biological molecules, has good compatibility with ethylene glycol chitosan, a biological molecule with antibacterial activity, and has excellent electronic conduction and signal amplification characteristics. The present invention combines the three substances through complex chemical bonds to form a hybrid material with a wider antibacterial range and enhanced antibacterial activity under visible light. The antibacterial range of the material of the present invention includes Gram-negative bacteria, Gram-positive bacteria and molds. The band gap of the obtained hybrid allows it to be active in the UV to infrared region, and it is environmentally friendly and low in cost.

[0098] The present invention studies the possible antibacterial mechanism of NiAl-LDH@ZnO / GCS composite materials based on the elements released during the antibacterial test. Potassium is released in the cell culture medium, indicating the presence of CS molecules, while nickel ions (Ni 2+) indicates that the active oxygen species (ZnO, Al2O3) are generated by the combination of ZnO, NiAl-LDH and CS. The NiAl-LDH prepared by the present invention has excellent ion release (Al2O3) protection, conduction and signal amplification properties, combining excellent film-forming properties, extremely strong microdynamic properties and biocompatibility of natural polymer chitosan. Positively charged (NH4 + The hybrid molecules with chitosan (a kind of metal oxide) interfere with the negatively charged bacterial cell membrane. This interaction with the bacterial membrane leads to changes in cell permeability and membrane lysis. The hybrid can activate the chelation of nutrients by chitosan, resulting in the inhibition of microbial growth by essential metals. The hybrid can also lyse microorganisms under light conditions by generating reactive oxygen species (ROS) through its metal compounds. The production of ROS is considered to be the main contributor to the antimicrobial activity of various metal oxides. Such reactive species are superoxide anions (O2), hydrogen peroxide (H2O2) and hydroxides (OH - ). The toxicity of these substances involves the destruction of cell components (such as lipids, DNA and proteins) due to their internalization into the bacterial cell membrane. Since the core-shell material has large pores, pathogenic microorganisms can be absorbed through its pores regardless of light or darkness.

[0099] Although the above-mentioned embodiments have made a detailed description of the present invention, they are only some embodiments of the present invention, rather than all embodiments. People can also obtain other embodiments based on the embodiments of the present invention without creative work, and these embodiments all fall within the scope of protection of the present invention.

Claims

1. A nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material, characterized in that: It is a core-shell structure, with ethylene glycol chitosan as the shell, encapsulating nickel aluminum hydrotalcite and zinc oxide.

2. The nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material according to claim 1, characterized in that: The mass ratio of the zinc oxide, ethylene glycol chitosan and nickel aluminum hydrotalcite is 1:4:6 to 1:8:

12.

3. The method for preparing the nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material according to claim 1 or 2, characterized in that: The following steps are involved: After dissolving ethylene glycol chitosan in an acidic solution, the mixture is mixed with nickel aluminum hydrotalcite and zinc oxide for self-assembly to obtain a colloidal solution; The colloidal solution is dried to obtain a nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material.

4. The preparation method according to claim 3, characterized in that: The acidic solution is an acetic acid solution, and the concentration of the acetic acid solution is 0.1-0.5 mol / L.

5. The preparation method according to claim 3, characterized in that: The drying temperature is 50-60° C. and the drying time is 6-12 hours.

6. The preparation method according to claim 3, characterized in that: The preparation method of the nickel-aluminum hydrotalcite comprises: Nickel chloride, aluminum hydroxide, water and urea are mixed to carry out a first hydrothermal reaction to obtain nickel aluminum hydrotalcite.

7. The preparation method according to claim 6, characterized in that: The molar ratio of nickel in the nickel chloride to aluminum in the aluminum hydroxide is 3:2 to 8:

3.

8. The preparation method according to claim 6, characterized in that: The temperature of the first hydrothermal reaction is 85-95° C. and the time is 12-15 hours.

9. The preparation method according to claim 6, characterized in that: The Cl formed by urea and nickel chloride - The molar ratio is 4:3 to 2:

1.

10. Use of the nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material according to claim 1 or 2 or the nickel-aluminum hydrotalcite-zinc oxide-ethylene glycol chitosan hybrid material obtained by the preparation method according to any one of claims 3 to 9 in the preparation of antibacterial materials.